Stelae as vehicles of expression: A regional study of gravestones from inland Asia Minor during the first and early second century AD - Cutten, Henry J. L. (2021)
This thesis investigates the expression of identity on funerary gravestones from 3 inland regions of Asia Minor during the early Imperial period. I focus on how the stela form functioned as a vehicle through which meaning was articulated and explore what was significant to contemporary inhabitants in the articulation and projection of their identity. My examinations consider the context behind this expression, accounting for a variety of influencing factors, in addition to self-agency. Through this analysis, I aim to determine how and why there appears to be homogeneity in appearance and expression across the catalogue (over definable areas), and what this suggests about the details communicated.